Barriers to Effective Listening to Lectures as Perceived by Undergraduate Students at Al al-Bayt University in Jordan - Al-Qudah, Khalid (Jordan Journal of Educational Sciences, 2007)
This study aimed to identify barriers to effective listening to lectures as perceived by undergraduate students at Al al-Bayt University in Jordan. The sample of the study consisted of 188 students (38 males and 150 females). A questionnaire was developed by the researcher to collect data. Mean, standard deviation and ANOVA analysis were used to analyze data. Results showed the four domains of the barriers to effective listening to lectures ordered by rank from the highest to the lowest as follows: (1) the educational environment, (2) the psychological conditions of students; (3) the instructor and (4) the physical conditions of students. Results also indicated there were no significant differences among students’ perceptions attributed to gender or the academic level. Results indicted significant difference attributed to the major of the respondents. Consequently, several recommendations were proposed to overcome barriers to effective listening to lectures.